Prenatal 2-D and 3-D Ultrasound Characteristics of a Case of Fetal Orofacial Macrocystic Lymphatic Malformation and its Postnatal Management with Intralesional Bleomycin - Elango, Nithya; Vikraman, Seneesh Kumar; Saranyadevi, A. C.; Sengodan, Chithra; Sengottiyan, Kumar Athapanur (Journal of Fetal Medicine, 2022)
Fetal lymphatic malformations (FLM) are benign hamartomatous lesions of the lymphatic vasculature usually localized in the cervicofacial and axillary regions and less frequently in the abdomen or inguinal areas, with an overall incidence of 1:6000 to 1:16,000 live births. FLM has a potential association with chromosomal aneuploidies such as Trisomy 21,18,13, Turner syndrome and genetic conditions such as Noonan syndrome, and with an excess risk for co-existing structural defects. A progressive increase in the dimensions of FLM's may result in polyhydramnios, hydrops, intrauterine fetal demise, airway obstruction and neonatal respiratory distress. We report a case of fetal orofacial lymphatic malformation detected in the mid-trimester anomaly scan with details of two- and three-dimensional imaging, prenatal counseling, cytogenetic workup, serial ultrasound surveillance, postnatal magnetic resonance imaging, and management with an intra-lesional sclerosing agent. The case depicts the strategic importance of multidisciplinary inputs in managing cases of prenatally diagnosed oral-cervical masses for optimizing perinatal outcome.
Keywords: Fetal tumors; Oro-facial lymphangioma; Bleomycin; Sclerosing agents; Prenatal diagnosis; 3D ultrasound